This close to okay : a novel - Cross-Smith, Leesa, 1978- (Grand Central Publishing, 2021)
"On a rainy October night in Kentucky, recently divorced therapist Tallie Clark is on her way home when she spots a man precariously standing on the edge of a bridge. Without a second thought, Tallie pulls over and jumps out of the car into the pouring rain. She convinces the man to join her for a cup of coffee, and he eventually agrees to come back to her house, where he finally, reluctantly, shares his first name: Emmett. Over the course of the emotionally-charged weekend that follows, Tallie makes it her mission to provide a safe and comfortable space for Emmett, although she doesn't confess that she works as a therapist. However, Emmett is not the only one who needs help - and he has secrets of his own. Alternating between Tallie and Emmett's perspectives as they inch closer to the truth of what brought Emmett to the bridge, This Close to Okay is an uplifting, powerful story of two strangers brought together by wild chance at the moment they need it the most."--Provided by publisher.